Modeling nanoindentation of TiCCaPON coating on Ti substrate using movable cellular automaton method; Computational Materials Science; Vol. 76 - Psakhie S. G. Sergey Grigorievich; Smolin A. Yu. Alexey Yurievich; Anikeeva G. M.; Shilko E. V. Evgeny Viktorovich; Pogozhev Yu. S.; Petrzhik M. I.; Levashov E. A. (2013, 2013)
Title screen